2006
DOI: 10.1128/jb.00194-06
|View full text |Cite
|
Sign up to set email alerts
|

Spx Is a Global Effector Impacting Stress Tolerance and Biofilm Formation inStaphylococcus aureus

Abstract: In Bacillus subtilis, Spx was recently characterized as a novel type of global regulator whose activity is regulated by the redox status of the cells. In the present study, we demonstrate that inactivation of Spx in the important pathogen Staphylococcus aureus renders the cells hypersensitive to a wide range of stress conditions including high and low temperature, high osmolarity, and hydrogen peroxide. Moreover, growth was restricted under nonstress conditions. Two-dimensional gel electrophoresis revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
178
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(192 citation statements)
references
References 54 publications
8
178
3
Order By: Relevance
“…In B. subtilis, the inactivation of the transcriptional regulator Spx, a known target of ClpXP proteolysis, suppressed phenotypes associated with clpP or clpX mutations, including poor growth, genetic competence, and sporulation frequency (34). Similar findings have been made in L. lactis and S. aureus (19,36), suggesting that the linkage of Spx accumulation with ClpXP phenotypes may be conserved between low-GC GPB. Here, we showed that the mutation of either of two spx orthologs, named spxA and spxB, was responsible, at least in part, for the attenuation of phenotypes associated with the loss of ClpXP proteolysis in S. mutans.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In B. subtilis, the inactivation of the transcriptional regulator Spx, a known target of ClpXP proteolysis, suppressed phenotypes associated with clpP or clpX mutations, including poor growth, genetic competence, and sporulation frequency (34). Similar findings have been made in L. lactis and S. aureus (19,36), suggesting that the linkage of Spx accumulation with ClpXP phenotypes may be conserved between low-GC GPB. Here, we showed that the mutation of either of two spx orthologs, named spxA and spxB, was responsible, at least in part, for the attenuation of phenotypes associated with the loss of ClpXP proteolysis in S. mutans.…”
Section: Discussionsupporting
confidence: 67%
“…More recently, Spx was shown to affect growth, general stress tolerance, and biofilm formation in S. aureus (36). Notably, unsuccessful attempts to isolate a clpP spx double mutant in S. aureus were reported, suggesting that the strain was not viable (36). The finding of the dual Spx regulators is particularly novel and may have broader implications since two or more copies of putative spx genes are also found in the genome of related streptococci, enterococci, and lactococci.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Spx of S. aureus was recently shown to fulfill an important role in growth, general stress protection, and biofilm formation (56). The existence of several Spx-like paralogs in a bacterium may indicate that competitive (or synergistic) interactions between these proteins and RpoA in response to cell envelope stress may be a general phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the importance of S. aureus biofilms in medical device-associated infections, a considerable amount of research has been directed at understanding the mechanisms of biofilm formation. Much of this research has focused on the bacterial mediators of biofilm formation (41,43,56,59), the environmental effectors of biofilm formation (26,28,50), and, more recently, the global changes that occur during biofilm development (2,44,45,60). The consensus from transcriptional profiling studies of S. aureus biofilms is that bacteria are growing microaerobically or anaerobically relative to planktonic cultures (2,45).…”
mentioning
confidence: 99%